Electromagnetic wave shielding film

By adopting a specific layer structure and a conductive adhesive layer design in the electromagnetic wave shielding film, the problem of rising connection resistance value after conductive particles is solved, and the superior transparency and low connection resistance value are achieved.

CN115004875BActive Publication Date: 2025-03-28TATSUTA ELECTRICWIRE & CABLE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180012297.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-26
Filing Date
2021-02-26
Publication Date
2025-03-28
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

When the existing electromagnetic wave shielding film mixes a large number of conductive particles in the conductive adhesive layer, it will cause problems such as rising connection resistance value and decreasing conductivity, making it difficult to achieve both superior transparency and low connection resistance value.

Method used

An electromagnetic wave shielding film with a specific layer structure includes a laminated structure of a first insulating layer, a silver nanowire layer, a second insulating layer and a conductive adhesive layer. The conductive adhesive layer contains a binder component and spherical or dendritic conductive particles, and the content ratio of the conductive particles is 1 to 80 mass%.

Benefits of technology

Even if a large number of conductive particles are compounded in the conductive adhesive layer, it is possible to maintain superior transparency and low connection resistance value, which solves the problem of lowering conductivity in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115004875B_ABST
    Figure CN115004875B_ABST
Patent Text Reader

Abstract

The present invention provides an electromagnetic wave shielding film having excellent transparency and low connection resistance even when a large amount of conductive particles are blended in a conductive adhesive layer. In the electromagnetic wave shielding film of the present invention, a first insulating layer, a silver nanowire layer, a second insulating layer, and a conductive adhesive layer are stacked in this order, the thickness of the second insulating layer is 50 to 500 nm, the conductive adhesive layer includes a binder component and spherical or dendritic conductive particles, and the content ratio of the conductive particles is 1 to 80% by mass relative to 100% by mass of the conductive adhesive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electromagnetic wave shielding film. More specifically, the present invention relates to an electromagnetic wave shielding film used in a printed wiring board. Background Art

[0002] Printed circuit boards are widely used to integrate circuits into mechanisms in electronic devices such as mobile phones, cameras, and notebook personal computers. They are also used to connect movable parts such as print heads and control parts. In these electronic devices, electromagnetic wave shielding measures are necessary, and even printed circuit boards used in devices use shielded printed circuit boards that implement electromagnetic wave shielding measures.

[0003] For the purpose of electromagnetic wave shielding measures, electromagnetic wave shielding films (hereinafter also referred to as "shielding films") are used in shielded printed circuit boards. For example, the shielding films used in conjunction with printed circuit boards contain a shielding layer such as a metal layer and a conductive bonding sheet provided on the surface of the shielding layer.

[0004] Shielding films containing conductive bonding sheets are known, for example, as disclosed in Patent Documents 1 and 2. The shielding film is used by bonding the exposed surface of the conductive bonding sheet to the surface of the printed circuit board, specifically, to the surface of the cover film provided on the surface of the printed circuit board. The conductive bonding sheet is usually bonded and laminated to the printed circuit board by thermocompression bonding under high temperature and high pressure conditions. The shielding film arranged on the printed circuit board in this way has the performance of shielding electromagnetic waves from outside the printed circuit board (shielding performance).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Publication No. 2015-110769;

[0008] Patent document 2: Japanese Patent Application Publication No. 2012-28334. Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] In recent years, when shielding films are attached to printed circuit boards, they are sometimes required to have easy alignment. Therefore, shielding films tend to be required to have transparency. Methods for improving transparency include using a thin transparent conductive layer in the conductive layer of the shielding film.

[0011] However, in conventional shielding films, the conductivity increases as the amount of conductive particles added to the conductive adhesive layer increases. However, in shielding films using a transparent conductive layer, if a large amount of conductive particles is added to the conductive adhesive layer, the connection resistance increases and the conductivity decreases.

[0012] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an electromagnetic wave shielding film having excellent transparency and low connection resistance even when a large amount of conductive particles is blended in a conductive adhesive layer.

[0013] Technical means to solve technical problems

[0014] The present inventors have made intensive studies to achieve the above object and have found that an electromagnetic wave shielding film having a specific layer structure can have excellent transparency and low connection resistance even when a large amount of conductive particles is blended in the conductive adhesive layer. The present invention has been completed based on this finding.

[0015] That is, the present invention provides an electromagnetic wave shielding film in which a first insulating layer, a silver nanowire layer, a second insulating layer, and a conductive adhesive layer are stacked in this order.

[0016] The thickness of the second insulating layer is 50 to 500 nm.

[0017] The conductive adhesive layer includes a binder component and spherical or dendritic conductive particles.

[0018] The content ratio of the conductive particles is 1 to 80% by mass relative to 100% by mass of the conductive adhesive layer.

[0019] It is preferable that the second insulating layer and the conductive adhesive layer are directly laminated.

[0020] Preferably, the second insulating layer is directly laminated on one surface with the conductive adhesive layer and is directly laminated on the other surface with the silver nanowire layer.

[0021] It is preferred that the content ratio of the conductive particles is 30 to 80% by mass relative to 100% by mass of the conductive adhesive layer.

[0022] It is preferred that the electromagnetic wave shielding film has a total light transmittance of 10% or more as measured by a method in accordance with JIS K 7361-1.

[0023] In addition, the present invention provides a shielding printed wiring board including the above-mentioned electromagnetic wave shielding film.

[0024] Effects of the Invention

[0025] The electromagnetic wave shielding film of the present invention can have excellent transparency and low connection resistance regardless of whether a small amount or a large amount of conductive particles are blended in the conductive adhesive layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026]

Figure 1

[0027] [Shielding film]

[0028] The shielding film of the present invention has a layer structure in which a first insulating layer, a silver nanowire layer, a second insulating layer, and a conductive adhesive layer are stacked in this order.

[0029] An embodiment of the shielding film of the present invention will be described below. Figure 1 It is a schematic cross-sectional view of one embodiment of the shielding film of the present invention. Figure 1 The shielding film 1 of the present invention includes a first insulating layer 11, a silver nanowire layer 12, a second insulating layer 13, and a conductive adhesive layer 14 in the following order.

[0030] (1st insulation layer)

[0031] The first insulating layer is a transparent substrate that functions as a protection for the silver nanowire layer and a support for the silver nanowire layer in the shielding film of the present invention. Examples of the first insulating layer include a plastic substrate (especially a plastic film), a glass plate, etc. The first insulating layer may be a single layer or a laminate of the same or different types.

[0032] The resin constituting the above-mentioned plastic substrate can be listed, for example, as low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylate (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and other polyolefin resins; polyurethane; polyethylene terephthalate (PE T), polyesters such as polyethylene naphthalate and polybutylene terephthalate (PBT); polycarbonate (PC); polyimide (PI); polyetheretherketone (PEEK); polyetherimide; polyamides such as aromatic polyamide and wholly aromatic polyamide; polyphenylene sulfide; polysulfone (PS); polyethersulfone (PES); acrylic resins such as polymethyl methacrylate (PMMA); acrylonitrile-butadiene-styrene copolymer (ABS); fluorocarbon resin; polyvinyl chloride; polyvinylidene chloride; cellulose resins such as triacetyl cellulose (TAC); silicone resin, etc. The above resins can be used alone or in combination. From the perspective of better transparency, polyester and cellulose resins are preferred, and polyethylene terephthalate and triacetyl cellulose are more preferred.

[0033] For the purpose of improving the adhesion and retention of the adjacent layers such as the silver nanowire layer, the surface of the first insulating layer (especially the surface on the silver nanowire layer side) may be subjected to physical treatments such as corona discharge treatment, plasma treatment, sandblasting treatment, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, etc.; chemical treatments such as chromic acid treatment; and surface treatments such as easy bonding treatment using a coating agent (primer). The surface treatment for improving adhesion is preferably applied to the entire surface of the first insulating layer on the silver nanowire layer side.

[0034] The thickness of the first insulating layer is not particularly limited, but is preferably 1 to 15 μm, and more preferably 3 to 10 μm. When the thickness is 1 μm or more, the shielding film can be more fully supported and the silver nanowire layer can be protected. When the thickness is 15 μm or less, the transparency and flexibility are excellent, and it is also economically advantageous. If the first insulating layer has a multiple-layer structure, the thickness of the first insulating layer is the total thickness of all layers.

[0035] (Silver nanowire layer)

[0036] The silver nanowire layer is an element that functions as a shielding layer in the shielding film of the present invention. The silver nanowire layer may be a single layer or a stack of layers of the same or different types.

[0037] The thickness of the silver nanowire layer is preferably 20 to 500 nm, more preferably 50 to 150 nm. When the thickness is 20 nm or more, high shielding performance can be maintained. When the thickness is 500 nm or less, the shielding film has excellent transparency. When the silver nanowire layer has a multiple-layer structure, the thickness of the silver nanowire layer is the total thickness of all layers.

[0038] (Second insulation layer)

[0039] The second insulating layer is a transparent layer that protects the silver nanowire layer. By placing the second insulating layer between the silver nanowire layer and the conductive adhesive layer, it is possible to suppress the reduction in transparency and connection stability. It is speculated that the above-mentioned reduction in transparency and connection stability is due to the friction with the conductive particles in the conductive adhesive layer, which causes damage to the silver nanowire layer. The second insulating layer can be a single layer or a plurality of layers.

[0040] The second insulating layer preferably includes a binder component. Examples of the binder component include thermoplastic resins, thermosetting resins, and active energy ray-curable compounds. Examples of the thermoplastic resins, thermosetting resins, and active energy ray-curable compounds include substances exemplified as binder components that may be included in the conductive adhesive layer described later. The binder component may be used alone or in combination of two or more.

[0041] The content of the binder component in the second insulating layer is not particularly limited, but is preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more relative to 100% by mass of the second insulating layer. When the content is 70% by mass or more, the flexibility is better, the embedding property into the small diameter hole is excellent, and the connection stability is better.

[0042] The second insulating layer may contain other components other than the above-mentioned binder component within the scope that does not impair the effect of the present invention. The above-mentioned other components can include, for example, curing agent, curing accelerator, plasticizer, flame retardant, defoaming agent, viscosity modifier, antioxidant, diluent, anti-settling agent, filler, leveling agent, coupling agent, ultraviolet absorber, tackifying resin, anti-adhesion agent, etc. The above-mentioned other components can be used alone or in combination of two or more.

[0043] The thickness of the second insulating layer is 50 to 500 nm, preferably 100 to 300 nm. When the thickness is 50 nm or more, shielding performance and connection stability are excellent. When the thickness is 500 nm or less, transparency and connection stability are excellent. If the second insulating layer is a multi-layer structure, the thickness of the second insulating layer is the sum of all layer thicknesses.

[0044] From the viewpoint of protecting the silver nanowire layer, the second insulating layer is preferably directly laminated on the conductive adhesive layer, and particularly preferably directly laminated on one surface with the conductive adhesive layer and on the other surface with the silver nanowire layer.

[0045] (Conductive adhesive layer)

[0046] The conductive adhesive layer has bonding properties for bonding the shielding film of the present invention to a printed circuit board and conductivity for electrically connecting to the silver nanowire layer. The conductive adhesive layer also functions as a shielding layer that exhibits shielding properties together with the silver nanowire layer. The conductive adhesive layer may be a single layer or multiple layers.

[0047] The conductive adhesive layer contains a binder component and spherical or dendritic (dendrite) conductive particles.

[0048] Examples of the binder component include thermoplastic resins, thermosetting resins, active energy ray-curable compounds, etc. The binder component may be used alone or in combination of two or more.

[0049] Examples of the thermoplastic resin include polystyrene resins, vinyl acetate resins, polyester resins, polyolefin resins (e.g., polyethylene resins, polypropylene resin compositions, etc.), polyimide resins, acrylic resins, etc. The thermoplastic resins may be used alone or in combination of two or more.

[0050] The thermosetting resin may include a thermosetting resin (thermosetting resin) and a resin obtained by curing the thermosetting resin. Examples of the thermosetting resin include phenolic resins, epoxy resins, polyurethane resins, polyurethane urea resins, melamine resins, alkyd resins, and the like. The thermosetting resin may be used alone or in combination of two or more.

[0051] Examples of the epoxy resin include bisphenol epoxy resins, spirocycle epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins, terpene epoxy resins, glycidyl ether epoxy resins, glycidyl amine epoxy resins, and novolac epoxy resins.

[0052] Examples of the bisphenol epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, and tetrabromobisphenol A epoxy resins. Examples of the glycidyl ether epoxy resins include tris(glycidyloxyphenyl)methane and tetra(glycidyloxyphenyl)ethane. Examples of the glycidylamine epoxy resins include tetraglycidyldiaminodiphenylmethane. Examples of the (linear) novolac epoxy resins include cresol (linear) novolac epoxy resins, phenol (linear) novolac epoxy resins, α-naphthol (linear) novolac epoxy resins, and brominated phenol (linear) novolac epoxy resins.

[0053] The active energy ray-curable compound can include compounds that can be cured by irradiation with active energy rays (active energy ray-curable compounds) and compounds obtained by curing the active energy ray-curable compounds. The active energy ray-curable compound is not particularly limited, and examples thereof include polymerizable compounds containing at least two free radical reactive groups (e.g., (meth)acryloyl groups) in the molecule. The active energy ray-curable compound can be used alone or in combination of two or more.

[0054] The adhesive component is preferably a thermosetting resin. In this case, after the shielding film of the present invention is placed on a printed wiring board for bonding to the printed wiring board, the adhesive component can be cured by applying pressure and heat, thereby achieving good bonding properties with the printed wiring board.

[0055] When the binder component includes a thermosetting resin, a curing agent for promoting a thermosetting reaction may also be included as a component constituting the binder component. The curing agent may be appropriately selected according to the type of the thermosetting resin. The curing agent may be used alone or in combination of two or more.

[0056] The content of the binder component in the conductive adhesive layer is not particularly limited, and is preferably 20 to 99% by mass, more preferably 30 to 80% by mass, and further preferably 40 to 70% by mass relative to the total amount 100% by mass of the conductive adhesive layer. When the content is 20% by mass or more, the close adhesion to the printed wiring board is better. When the content is 99% by mass or less, the conductive particles can be fully contained.

[0057] The conductive particles include spherical conductive particles and / or dendritic conductive particles. By using the spherical or dendritic conductive particles, even when a large amount of conductive particles are mixed, excellent transparency and excellent connection stability can be achieved. Regarding the conductive particles, from the viewpoint of better connection stability, the conductive particles are preferably dendritic conductive particles. In addition, from the viewpoint of excellent transparency of the shielding film, the conductive particles are preferably spherical conductive particles.

[0058] Examples of the conductive particles include metal particles, metal-coated resin particles, and carbon-based fillers. The conductive particles may be used alone or in combination of two or more.

[0059] Examples of the metal constituting the coating portion of the metal particles and the metal-coated resin particles include gold, silver, copper, nickel, zinc, etc. The metals may be used alone or in combination of two or more.

[0060] Specifically, the metal particles include, for example, copper particles, silver particles, nickel particles, silver-coated copper particles, gold-coated copper particles, silver-coated nickel particles, gold-coated nickel particles, silver-coated alloy particles, etc. The silver-coated alloy particles include, for example, silver-coated copper alloy particles obtained by coating alloy particles containing copper (for example, copper alloy particles composed of an alloy of copper, nickel, and zinc) with silver, etc. The metal particles can be produced by electrolysis, atomization, reduction, etc.

[0061] Among them, the metal particles are preferably silver particles, silver-coated copper particles, and silver-coated copper alloy particles. Silver-coated copper particles and silver-coated copper alloy particles are particularly preferred from the viewpoints of excellent conductivity, ability to suppress oxidation and coagulation of the metal particles, and reduced cost of the metal particles.

[0062] The median diameter (D50) of the conductive particles is not particularly limited, but is preferably 5 to 15 μm, and more preferably 5 to 10 μm. The median diameter is the median diameter of all spherical conductive particles and / or dendritic conductive particles in the conductive adhesive layer, and refers to the particle size at 50% of the cumulative value in the particle size distribution obtained by the laser diffraction / scattering method. By making the median diameter within the above range, the connection stability in the present invention using conductive particles is better. The median diameter can be measured, for example, by a laser diffraction particle size analyzer (trade name "SALD-2200", manufactured by Shimadzu Corporation).

[0063] The content of the conductive particles in the conductive adhesive layer is 1 to 80% by mass, preferably 20 to 70% by mass, and more preferably 30 to 60% by mass, relative to 100% by mass of the conductive adhesive layer. In the shielding film of the present invention, the conductive adhesive layer has a low connection resistance value and excellent connection stability regardless of whether it includes a small amount of the conductive particles of about 1% by mass or a large amount of the conductive particles of up to 80% by mass.

[0064] In the range that does not impair the effect of the present invention, the conductive adhesive layer may also contain other ingredients other than the above-mentioned components. The above-mentioned other ingredients can list well-known and even commonly used adhesive layer components. The above-mentioned other ingredients can, for example, list curing accelerators, plasticizers, flame retardants, defoamers, viscosity modifiers, antioxidants, diluents, anti-settling agents, fillers, leveling agents, coupling agents, ultraviolet absorbers, tackifying resins, anti-adhesion agents, etc. The above-mentioned other ingredients can be used only one, or two or more. And relative to 100 parts by mass of spherical conductive particles and / or dendritic conductive particles, the content of conductive particles other than spherical conductive particles and dendritic conductive particles is, for example, less than 10 parts by mass, preferably less than 5 parts by mass, and more preferably less than 1 part by mass.

[0065] The thickness of the conductive adhesive layer is not particularly limited, but is preferably 3 to 20 μm, and more preferably 5 to 15 μm. When the thickness is 3 μm or more, shielding performance is better. When the thickness is 20 μm or less, the surface of the conductive particles tends to be closer to the layer surface or exposed from the surface, and connection stability is better.

[0066] The ratio of the thickness of the conductive adhesive layer to the D50 of the conductive particles [adhesive layer thickness / D50] is not particularly limited, but is preferably 0.2 to 1.5, and more preferably 0.5 to 1.0. When the ratio is 0.2 or more, the bonding property to the bonded object such as a printed wiring board is better. When the ratio is 1.5 or less, the amount of conductive particles exposed from the surface of the conductive adhesive layer is large, and the connection stability is better.

[0067] The shielding film of the present invention may also contain a separator (peeling film) on the conductive adhesive layer side. The separator is laminated in a manner that allows it to be peeled off from the shielding film of the present invention. The separator is an element that covers and protects the conductive adhesive layer and is peeled off when the shielding film of the present invention is used.

[0068] Examples of the separator include polyethylene terephthalate (PET) films, polyethylene films, polypropylene films, and plastic films or papers whose surfaces are coated with a release agent such as a fluorine-based release agent or a long-chain alkyl acrylate-based release agent.

[0069] The thickness of the separator is preferably 10 to 200 μm, more preferably 15 to 150 μm. When the thickness is 10 μm or more, the protective performance is better. When the thickness is 200 μm or less, the separator is easy to peel off during use.

[0070] The shielding film of the present invention may also contain other layers besides the first insulating layer, the silver nanowire layer, the second insulating layer and the conductive adhesive layer. Examples of the other layers include other insulating layers, anti-reflection layers, anti-glare layers, anti-fouling layers, hard coating layers, ultraviolet absorbing layers, and anti-Newton ring layers.

[0071] The shielding film of the present invention has excellent transparency. The total light transmittance of the shielding film of the present invention in the measurement method according to JIS K 7361-1 is preferably 10% or more, more preferably 20% or more, further preferably 50% or more, and particularly preferably 65% ​​or more. The total light transmittance can be measured using a well-known spectrophotometer. The total light transmittance is measured for a laminate having the first insulating layer and the conductive adhesive layer as the two end layers.

[0072] The haze value of the shielding film of the present invention in the measurement method according to JIS K 7361-1 is preferably 95% or less, more preferably 92% or less, and further preferably 90% or less. The haze value can be measured using a well-known spectrophotometer. The haze value is measured for a laminate having the first insulating layer and the conductive adhesive layer as the end layers.

[0073] The shielding film of the present invention is preferably used for a printed circuit board, and is particularly preferably used for a flexible printed circuit board (FPC). The shielding film of the present invention can make the connection resistance value low regardless of whether a small amount of conductive particles are mixed in the conductive adhesive layer or a large amount of conductive particles are mixed. It also has excellent transparency and is easy to align on the printed circuit board. Therefore, the shielding film of the present invention can be well used as an electromagnetic wave shielding film for a flexible printed circuit board.

[0074] (Method for producing electromagnetic wave shielding film)

[0075] A method for producing the shielding film of the present invention will be described.

[0076] exist Figure 1 In the manufacturing process of the shielding film 1 of the present invention, the silver nanowire layer 12 is first formed on the first insulating layer 11. The silver nanowire layer 12 can be formed by laminating the silver nanowire layer 12 on the surface of the first insulating layer 11.

[0077] Next, the second insulating layer 13 can be formed by, for example, applying (coating) a resin composition for forming the second insulating layer 13 on the surface of the formed silver nanowire layer 12 , and removing the solvent and / or partially curing the resin composition as necessary.

[0078] The resin composition may include, for example, a solvent in addition to the components included in the second insulating layer. Examples of the solvent include toluene, acetone, methyl ethyl ketone, methanol, ethanol, propanol, ethyl acetate, propyl acetate, butyl acetate, dimethylformamide, and the like. The solid content concentration of the resin composition may be appropriately set according to the thickness of the second insulating layer to be formed, and the like.

[0079] The resin composition can be applied by a well-known coating method, for example, a coating machine such as a gravure roll coater, a reverse roll coater, an oiling roll coater, a lip coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, a direct coater, or a slit coater can be used.

[0080] Next, the conductive adhesive layer 14 can be formed by applying (coating) the adhesive composition for forming the conductive adhesive layer 14 on the surface of the formed second insulating layer, and removing the solvent and / or partially curing the conductive adhesive layer 14 as necessary.

[0081] The adhesive composition may further include a solvent (solvent) in addition to the components contained in the conductive adhesive layer. The solvent may include the substances exemplified as the solvent that the resin composition may include. The solid content concentration of the adhesive composition may be appropriately set according to the thickness of the conductive adhesive layer to be formed.

[0082] The adhesive composition can be applied by a known coating method, for example, a coating machine used for coating the resin composition can be used.

[0083] In the above-mentioned manufacturing method, a method of sequentially forming each layer (direct coating method) is described, but it is not limited to the above-mentioned method. For example, it can be produced by stacking each layer formed individually on a temporary substrate such as a release film or a substrate and sequentially bonding them (stacking method).

[0084] The shielding film of the present invention can be used to make a printed circuit board. For example, the conductive adhesive layer of the shielding film of the present invention is bonded to a printed circuit board (e.g., a cover film), thereby obtaining a shielded printed circuit board having the shielding film of the present invention bonded to the printed circuit board. In the above-mentioned shielded printed circuit board, the above-mentioned conductive adhesive layer can also be thermally cured. Example

[0085] The present invention will be described in further detail below based on examples, but the present invention is not limited to these examples. The content ratio of the conductive particles in the table indicates the ratio in the conductive adhesive layer.

[0086] Comparative Example 1

[0087] A silver nanowire layer (wire diameter 30nm, wire length 20μm, thickness about 70nm) was laminated on the surface of a PET film (thickness 6μm). Then, an adhesive composition obtained by mixing an epoxy resin solution and conductive particles A was applied to the surface of the silver nanowire layer using a wire rod, and heated at 120°C for 1 minute to form a conductive adhesive layer (thickness 5μm). The shielding film of Comparative Example 1 was prepared as above. The blending amount of the epoxy resin solution and the conductive particles A was set to an amount in which the proportion of the epoxy resin in the conductive adhesive layer was 70% by mass and the proportion of the conductive particles A was 30% by mass.

[0088] Comparative Examples 2, 3

[0089] Each shielding film was produced in the same manner as in Comparative Example 1 except that the kind and content ratio of the conductive particles were changed as shown in Table 1.

[0090] Example 1

[0091] A silver nanowire layer (wire diameter 30nm, wire length 20μm, thickness about 70nm) was stacked on the surface of a PET film (thickness 6μm). Next, a polyester resin composition was applied to the surface of the silver nanowire layer using a wire rod, and heated at 100°C for 1 minute, thereby forming a resin layer (thickness 50nm). Then, an adhesive composition obtained by mixing an epoxy resin solution and conductive particles A was applied to the surface of the resin layer using a wire rod, and heated at 120°C for 1 minute, thereby forming a conductive adhesive layer (thickness 5μm). The shielding film of Example 1 was prepared as above. The mixing amount of the epoxy resin solution and the conductive particles A was set to an amount in which the proportion of the epoxy resin in the conductive adhesive layer was 70% by mass and the proportion of the conductive particles A was 30% by mass.

[0092] Examples 2, 3 and Comparative Example 4

[0093] Each shielding film was produced in the same manner as in Example 1 except that the thickness of the resin layer was changed as shown in Table 1.

[0094] Example 4

[0095] Except having changed the content ratio of electroconductive particle as shown in Table 1, it carried out similarly to Example 1, and produced the shielding film.

[0096] Examples 5, 6 and Comparative Example 5

[0097] Each shielding film was produced in the same manner as in Example 4 except that the thickness of the resin layer was changed as shown in Table 1.

[0098] Example 7

[0099] Except having changed the kind of electroconductive particle as shown in Table 1, it carried out similarly to Example 1, and produced the shielding film.

[0100] Examples 8, 9 and Comparative Example 6

[0101] Each shielding film was produced in the same manner as in Example 7 except that the thickness of the resin layer was changed as shown in Table 1.

[0102] (evaluate)

[0103] The shielding films obtained in the examples and comparative examples were evaluated as follows. The evaluation results are shown in the table. Only the PET film (thickness 6 μm) was used as the evaluation object of reference example 1. In addition, "OL" in the table indicates a value exceeding the measurement limit of 100Ω due to overload.

[0104] (1) Connection resistance value

[0105] Prepare the following printed circuit substrate: two copper foil patterns (4 mm wide, 1 mm spacing) similar to the ground pattern are formed on the base component composed of polyimide film, and a covering film (insulating film) composed of an insulating adhesive layer and a polyimide film is formed thereon. A gold plating layer is provided on the surface of the copper foil pattern as a surface layer. A circular opening with a diameter of 0.8 mm is formed on the covering film to simulate the ground connection portion. Use a press to join the shielding film and the printed circuit substrate made in each embodiment and comparative example under the conditions of temperature: 170°C, time: 30 minutes, and pressure: 2 to 3 MPa. After joining the shielding film, the resistance value between the two copper foil patterns is measured with a resistance meter, and the connectivity between the copper foil pattern and the conductive bonding sheet is evaluated as the connection resistance value.

[0106] (2) Total light transmittance

[0107] The shielding films obtained in Examples and Comparative Examples were measured using a haze meter (trade name “NDH4000”, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7361-1, with the PET film surface on the integrating sphere side being irradiated with measuring light.

[0108] [Table 1]

[0109]

[0110] When a silver nanowire layer is used as a transparent conductive layer, the shielding film of the present invention can achieve high total light transmittance, excellent transparency, low connection resistance, and excellent connection stability even when a large amount of conductive particles is mixed up to 30 to 50% by mass (Examples 1 to 9). In addition, compared with the case where dendritic conductive particles are used (Examples 7 to 9), there is a tendency for high total light transmittance and excellent transparency when spherical conductive particles are used (Examples 1 to 6). On the other hand, compared with the case where spherical conductive particles are used (Examples 1 to 6), there is a tendency for low connection resistance and excellent connection stability when dendritic conductive particles are used (Examples 7 to 9). In the case where there is no resin layer between the silver nanowire layer and the conductive adhesive layer (Comparative Examples 1 to 3), under the condition of a large amount of mixing of 30% by mass or more, the result is a high connection resistance value compared with the case where the same conductive particles are used in the same proportion (Examples 1 to 9).

[0111] Number Description

[0112] 1 Shielding film

[0113] 11. First insulation layer

[0114] 12 Silver Nanowire Layer

[0115] 13 Second insulation layer

[0116] 14 Conductive adhesive layer

Claims

1. An electromagnetic wave shielding film, characterized in that: The first insulating layer, the silver nanowire layer, the second insulating layer, and the conductive adhesive layer are stacked in this order; The first insulating layer is a transparent substrate; The second insulating layer is a transparent layer with a thickness of 50 to 300 nm; The conductive adhesive layer includes a binder component and spherical or dendritic conductive particles; The content ratio of the conductive particles is 20 to 70% by mass relative to 100% by mass of the conductive adhesive layer.

2. The electromagnetic wave shielding film according to claim 1, characterized in that: The second insulating layer and the conductive adhesive layer are directly laminated.

3. The electromagnetic wave shielding film according to claim 1, characterized in that: The second insulating layer is directly laminated on one surface with the conductive adhesive layer and is directly laminated on the other surface with the silver nanowire layer.

4. The electromagnetic wave shielding film according to claim 1, characterized in that: The thickness of the second insulating layer is 50 to 200 nm.

5. The electromagnetic wave shielding film according to claim 1, characterized in that: The content ratio of the conductive particles is 30 to 50% by mass relative to 100% by mass of the conductive adhesive layer.

6. The electromagnetic wave shielding film according to any one of claims 1 to 5, characterized in that: The total light transmittance measured in accordance with the method of JIS K 7361-1 is 10% or more.

7. A shielded printed circuit board, characterized in that: The shielding printed circuit board comprises the electromagnetic wave shielding film according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Anisotropic conductive film and method of manufacturing connecting structure

    JP2012028334A

  • Conductive adhesive, conductive adhesive sheet, wiring device, and method for manufacturing wiring device

    JP2015110769A

  • Method for manufacturing electromagnetic shielding film and electromagnetic shielding film manufactured thereby

    CN103120042A

  • Electromagnetic shielding film, preparation method thereof and display device

    CN109575827A